A porous Zn(II)-based metal–organic framework for highly selective and sensitive Fe3+ ion detection in water. (1st June 2018) - Sun, Meng-Yao; Chen, Di-Ming
Graphical abstract: A new highly porous metal–organic framework was obtained using a mix-ligand approach. Single crystal X-ray structural analysis shows that compound1 is composed of 1D helical Zn-triazolate chain building units that connected by the deprotonated bpydbH2 ligand to form a (3, 4, 6)-connected net. Due to its strong fluorescent emission and high porosity, compound1 could behave as a chemosensor for selective detection of Fe 3+ ion with high selectivity and sensitivity in water. In connection to this, the detection mechanism and the host–guest interaction have also been investigated via computational analysis. Abstract: A new highly porous metal–organic framework, namely [Zn3 (bpydb)2 (atz)2 (DMF)](DMF)6 n, was solvothermally synthesized using 4, 4′-(4, 4′-bipyridine-2, 6-diyl) dibenzoic acid (bpydbH2 ), 3-amino-1, 2, 4-triazole (Hatz) and Zn(NO3 )2 ·6H2 O as the starting materials. Single crystal X-ray structural analysis shows that compound1 is composed of 1D helical Zn-triazolate chain building units that connected by the deprotonated bpydbH2 ligand to form a (3, 4, 6)-connected net. Due to its strong fluorescent emission and high porosity, compound1 could behave as a chemosensor for selective detection of Fe 3+ ion with high selectivity and sensitivity in water. In connection to this, the detection mechanism and the host–guest interaction have also been investigated via computational analysis.